Effect of vagotomy on the duodenal mechanisms regulating gastric secretion (Revista Española de Fisiología, 1987)
Gastric acid secretion, gastrin and secretin serum levels after duodenal acidification were studied in 6 dogs, before and after a troncular vagotomy was performed in each one.After duodenal acidification in normal dogs, a 45.2% inhibition of gastric acid secretion with parallel 55-84% increases in the serum secretin levels, without changes in the serum gastrin levels, was noted.When a troncular vagotomy was performed in the same dogs, duodenal acidification produced a 20% (non significant) inhibition of gastric acid secretion with parallel 34-72% increases in the serum secretin levels and without changes in the serum gastrin levels.It is concluded that vagus nerve is necessary to assess a physiological inhibition of gastric secretion after duodenal acidification and it is suggested that humoral and nervous factors are implicated and coexist in these mechanisms.